Classical Guidance Service Tools to Increase the Creativity of Junior High School Students - Khilmi Mustofa; I Ketut Gading; Dewi Arum Widhiyanti Metra Putri (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The low creativity of students is due to the need for more guidance provided by teachers and counselors, so to overcome these problems, guidance service tools are needed to maximize the development of children's creativity. This study aims to produce a classical guidance service toolkit to increase the creativity of junior high school students. This research belongs to the development research developed using the 4-D development model. The 4-D development model comprises the define, design, development, and dissemination stages. The subjects involved in this study were three lecturers as experts and two guidance and counseling teachers as practitioners. Collecting data in the study was carried out using observation, interviews, and questionnaires. The instrument used is in the form of a student creativity questionnaire. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques through the normality test, homogeneity test, and t-test. The results of data analysis in the study showed that the t-test score was 2.710, and sig. (2-tailed) was 0.009 <0.05, meaning H0 is rejected, and Ha is accepted. Based on these results, the classical guidance service tool effectively increases the creativity of junior high school students.